Orogenic lithosphere and slabs in the greater Alpine area – interpretations based on teleseismic P-wave tomography - M. R. Handy (Copernicus Publications, 2021)
Based on recent results of AlpArray, we propose a new model of Alpine collision that involves subduction and detachment of thick (∼ 180 km) European lithosphere. Our approach combines teleseismic P-wave tomography and existing local earthquake tomography (LET), allowing us to image the Alpine slabs and their connections with the overlying orogenic lithosphere at an unprecedented resolution. The images call into question the conventional notion that downward-moving lithosphere and slabs comprise only seismically fast lithosphere. We propose that the European lithosphere is heterogeneous, locally containing layered positive and negative Vp anomalies of up to 5 %–6 %. We attribute this layered heterogeneity to seismic anisotropy and/or compositional differences inherited from the Variscan and pre-Variscan orogenic cycles rather than to thermal anomalies. The lithosphere–asthenosphere boundary (LAB) of the European Plate therefore lies below the conventionally defined seismological LAB. In contrast, the lithosphere of the Adriatic Plate is thinner and has a lower boundary approximately at the base of strong positive Vp anomalies at 100–120 km.